GENOMIC MEDICINE AND PERSONALIZED MANAGEMENT OF SEPSIS - P. I. Mironov; A. U. Lekmanov (Вестник анестезиологии и реаниматологии, 2018)
The review is devoted to one of the most critical issues of modern intensive care – personalized management of sepsis. The current definition of genomics has been given, and data available on the above issue have been analyzed, advantages and limitations of this approach in the intensive care have been discussed. The special emphasis is put on the prospect of using genetic biomarkers for sepsis severity score and prediction of sepsis outcome.